Syphilis in pregnant women in the municipality of Catanduvas-SC - R. S. Weber; G. C. M. Berber; P. Z. Tomasi; V. Beltrame (Scientific Electronic Archives, 2019)
This is a retrospective, cross-sectional, documentary study aimed at analyzing the behavior of health professionals who perform prenatal care in pregnant women in the basic network of the Municipality of Catanduvas SC, from January to December 2016. We analyzed 97 medical records. The results show that the average age of pregnant women was 28 years, and 47.4% were aged between 20 and 29 years. The onset of prenatal care occurred in the second trimester in 55.7% of pregnant women; 50.5% performed 1 to 3 nursing consultations and 45.5% performed 7 or more medical visits. It was also observed that 91.8% of the pregnant women performed laboratory tests and three rapid tests for the diagnosis of Syphilis, Viral Hepatitis, and HIV, being a test in each gestational trimester. During the analyzed period two pregnant women with syphilis were diagnose , which gives us a prevalence rate of 2.1%, which were treated properly, but one of the partners did not accept the treatment.  It should be pointed out that data referring to the characteristics of the pregnant women did not have a 100% completion which leads us to suggest that the professionals involved in the prenatal care receive continuous education about the importance of correct filling of the pregnant woman's chart, emphasizing that this is a legal procedure and that the non-fulfillment can jeopardize the continuity of the assistance and the carrying out of researches in the area.